THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT PT.BANK MANDIRI (PERSERO) TBK. KCP TANGERANG STPI CURUG - Kusmanto Kusmanto; Subandriyo Subandriyo; Eva April Liani (SEAN Institute, 2023)
The purpose of this study is to determine the level of influence of Service Quality on Customer Satisfaction. The research method used is explanatory research with a quantitative approach. The population in this study were 264 customers. The sampling technique used Accidental Sampling with a sample size of 73 customers obtained using the Slovin formula. Data collection was carried out using a questionnaire with a Likert scale. The analysis method used in this research is simple linear regression analysis method with SPSS 25 for Windows application. From the results of data analysis, the result of the correlation coefficient level between the service quality variable on customer satisfaction is 0.717 which means the level of relationship is strong. Based on the research results, it is proven that service quality has an effect of 51.5% on customer satisfaction, while the remaining 48.5% is influenced by other factors not examined in this study. Based on the results of the hypothesis test obtained with the value of t count> t table or 8.678> 1.993 with a probability value of 0.000 <0.05, which means it is proven that the service quality variable has a positive and significant effect on customer satisfaction.